2018
DOI: 10.1177/0269215518773442
|View full text |Cite
|
Sign up to set email alerts
|

Does Tai Chi improve balance and reduce falls incidence in neurological disorders? A systematic review and meta-analysis

Abstract: Tai Chi is effective in reducing falls incidence in Parkinson's disease and stroke. This systematic review did not find high-quality studies among other neurological disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
2
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(46 citation statements)
references
References 31 publications
(80 reference statements)
1
41
2
1
Order By: Relevance
“…Tai Chi has the beneficial effect on balance and mobility in PD [42], and it is also effective in reducing falls incidence [ [43][44][45]; however, the effect of Tai Chi on FoG was not studied.…”
Section: Discussionmentioning
confidence: 99%
“…Tai Chi has the beneficial effect on balance and mobility in PD [42], and it is also effective in reducing falls incidence [ [43][44][45]; however, the effect of Tai Chi on FoG was not studied.…”
Section: Discussionmentioning
confidence: 99%
“…The PEDro scale is an 11-item scale that has been previously used in systematic reviews. 19 , 20 Any disagreements were resolved via discussion or consultation with the fourth author (KJS).…”
Section: Methodsmentioning
confidence: 99%
“…Oriental martial arts, such as tai chi, have been successfully used in treatment of individuals with Parkinson's disease. Tai chi combines deep breathing and slow movements and studies have provided moderate evidence that tai chi improves balance and functional mobility, reducing the number of falls, but with no significant effect in gait velocity, step length, and gait endurance improvement [33,60,61]. A systematic review and meta-analysis showed that tai chi, plus medication, showed greater gains than medication alone or another therapy plus medication in motor function and balance.…”
Section: Aerobic Training: Treadmill Cycling Free Walking Dance Amentioning
confidence: 99%